2022
DOI: 10.1038/s41598-022-25529-z
|View full text |Cite
|
Sign up to set email alerts
|

The evolutionary process of invasion in the fall armyworm (Spodoptera frugiperda)

Abstract: The fall armyworm (FAW; Spodoptera frugiperda) is one of the major agricultural pest insects. FAW is native to the Americas, and its invasion was first reported in West Africa in 2016. Then it quickly spread through Africa, Asia, and Oceania, becoming one of the main threats to corn production. We analyzed whole genome sequences of 177 FAW individuals from 12 locations on four continents to infer evolutionary processes of invasion. Principal component analysis from the TPI gene and whole genome sequences shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 85 publications
(129 reference statements)
1
13
0
Order By: Relevance
“…Our f-branch results also indicate gene flow between the two genetic clusters (Figure 4b), which aligns with the field conditions in the Americas (Dumas, 2015). Our phylogenetic results, along with previous studies, suggest that the rice strain may represent an earlier divergent population (Fiteni et al, 2022;Yainna et al, 2022). Previous studies have reported detection of rice-strain Tpi in the Eastern hemisphere based on a single site, TpiE-183 (Jing et al, 2020;Tay et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our f-branch results also indicate gene flow between the two genetic clusters (Figure 4b), which aligns with the field conditions in the Americas (Dumas, 2015). Our phylogenetic results, along with previous studies, suggest that the rice strain may represent an earlier divergent population (Fiteni et al, 2022;Yainna et al, 2022). Previous studies have reported detection of rice-strain Tpi in the Eastern hemisphere based on a single site, TpiE-183 (Jing et al, 2020;Tay et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies based on above two markers have indicated that the invasive FAW exhibit hybrid genotypes, with a predominant corn-strain ratio based on the Tpi marker (Nagoshi et al, 2019(Nagoshi et al, , 2022Zhang et al, 2020). Subsequent genome-wide analysis supported the notion that invasive populations were mainly of corn-strain genetic background (Yainna et al, 2022;Zhang et al, 2020). However, a divergent Tpi haplotype has been detected, with 10 unique single nucleotide polymorphisms (SNPs) compared to previously reported corn-or rice-strain genotype in the Americas, suggesting a more complex genetic differentiation of invasive populations (Nagoshi, 2019;Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Genome-wide SNP loci demonstrated that invasive FAW populations from SEA and Australia exhibited admixed genomic signatures similar to that observed in other invasive populations 33,34 . While the current invasive populations in Africa and Asia likely arrived already as hybrids as suggested by Yainna et al 68 , the Malaysia Kedah State population was potentially established by offspring of a non-admixed female. Distinct admixture patterns in Malaysian FAW populations between Kedah and Johor/Penang states therefore suggested that establishment of these populations was likely as separate introduction events.…”
Section: Admixture Analysismentioning
confidence: 92%